Improving Students' Vocabulary by Using the Cake Application at Senior High School 9 Makassar - Firman Saputra Sattuang; Haryanto Haryanto; Munir Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to improve the vocabulary of grade students of SMA Negeri 9 Makassar. This study uses a pre-experimental design with a quantitative approach. The study population was 36 grade X.3 students of SMA Negeri 9 Makassar. Data collection techniques used were pre-test, treatment, and post-test. The statistical results of the students' average scores increased significantly from 74.72 in the pre-test to 91.39 in the post-test. The t-test results showed a significant difference before and after treatment, with a significance value of 0.000. These results support the use of the cake application to improve students' vocabulary in English learning.Keywords: Vocabulary, Cake Application, Learning Media.